Identification and Characterization of a High-Affinity Choline Uptake System of Brucella abortus - Herrmann, Claudia K. (American Society for Microbiology, 2013)
Phosphatidylcholine (PC), a common phospholipid of the eukaryotic cell membrane, is present in the cell envelope of the intracellular pathogen Brucella abortus, the etiological agent of bovine brucellosis. In this pathogen, the biosynthesis of PC proceeds mainly through the phosphatidylcholine synthase pathway; hence, it relies on the presence of choline in the milieu. These observations imply that B. abortus encodes an as-yet-unknown choline uptake system. Taking advantage of the requirement of choline uptake for PC synthesis, we devised a method that allowed us to identify a homologue of ChoX, the high-affinity periplasmic binding protein of the ABC transporter ChoXWV. Disruption of the choX gene completely abrogated PC synthesis at low choline concentrations in the medium, thus indicating that it is a high-affinity transporter needed for PC synthesis via the PC synthase (PCS) pathway. However, the synthesis of PC was restored when the mutant was incubated in media with higher choline concentrations, suggesting the presence of an alternative low-affinity choline uptake activity. By means of a fluorescence-based equilibrium-binding assay and using the kinetics of radiolabeled choline uptake, we show that ChoX binds choline with an extremely high affinity, and we also demonstrate that its activity is inhibited by increasing choline concentrations. Cell infection assays indicate that ChoX activity is required during the first phase of B. abortus intracellular traffic, suggesting that choline concentrations in the early and intermediate Brucella-containing vacuoles are limited. Altogether, these results suggest that choline transport and PC synthesis are strictly regulated in B. abortus.